Demand for emergency services during the COVID-19 pandemic and disease burden: a case study in Portugal - Alcina Nunes; Catarina Costa; João P. Martins; João P. Martins; Pedro L. Ferreira; Pedro L. Ferreira; Rui Pimenta; Rui Pimenta (Frontiers Media S.A., 2024)
BackgroundThe COVID-19 pandemic brought changes in the pattern of care use. A significant increase in the volume of emergencies was expected. However, a significant decrease was observed worldwide.MethodsAn observational, analytical and cross-sectional study of all records of emergency episodes of patients aged 18 years or older admitted to the emergency services of the University of Porto Hospital Centre (2018-2022) were analysed.ResultsDuring the pandemic, a significant reduction in emergency episode admissions (up to 40% during lockdowns), an increase in pre-emergency services, and discharges from Infectious Diseases and Internal Medicine was observed. The discharges from General Practice and General Practice and Family Medicine were residual.ConclusionThe lower use and type of use of emergency services during the COVID-19 pandemic had a negative impact on the disease burden. This could be prevented in future pandemics through the development of strategies to promote confidence in the use of health resources and establishing contingency plans for virtual assistance.